Evaluation of Liquid Based Cytology (LBC) and Conventional Pap’s Smear Test as Methods of Cervical Cancer Screening - Chowdhury, Mehdi Ashik; Barua, Asim Ranjan; Asaduzzaman, -; Hoque, Mohammad Mahabubul; Rahman, DM Arifur (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Cervical cancer screening can actually prevent most cervical cancers and also facilitates early detection which allows fruitful treatment. Objective: To evaluate and compare the efficacy of Liquid-based cytology (LBC) with conventional Pap smear test. Methods: This crosssectional study was conducted between March 2015 and June 2017. A total of 72 women participated in this study attending the Out-Patient Department (OPD) of Gynaecology (Colposcopy Clinic) of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, for VIA test. The smears prepared by the conventional Pap smear method and Liquid-based cytology method were observed by two independent observers in Department of Pathology of the same institution. Results: The mean age of the patients was 40.22±12.29 years. Considering histopathology as gold standard, in conventional Pap smear preparation our data suggested its sensitivity 87.5%, specificity 92.2%, accuracy 91.7%, positive predictive value 58.3% and negative predictive value 98.3%. In contrast, in Liquid-based cytology, we found its sensitivity 75.0%, specificity 90.6%, accuracy 88.9%, positive predictive value 50.0% and negative predictive value 96.7%. Conclusion: LBC has practical advantages over conventional preparation by producing monolayer of cells, smaller area to screen, reproducibility and availability of doing adjunct molecular techniques from residual sample. However, conventional preparation shows better sensitivity and positive predictive value and almost similar specificity, negative predictive value and accuracy with LBC. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 36-40